Optimization Study of Gear Oil-air Lubrication Parameters Based on Orthogonal Test Method - Chang Lu; Qi Chen; Qingwei Hou; Zhaqiang Tang (Jixie chuandong)
In order to provide a feasible lubrication means under starved condition， the gear transmission effect and the optimal oil-air parameters using oil-air lubrication are explored. Through the design of a five-level orthogonal test， the lubrication influence degree and tooth surface temperature， which are caused by oil supply， air supply and nozzle height， are analyzed under different speeds and load conditions. Then the optimal level setting and optimal solution of oil-gas parameters are obtained. These parameters are used in a comparative test between oil-air lubrication and splash lubrication. The results show that the air supply has the greatest influence on the oil-air lubrication effect， and there is an optimal air supply quantity； the influence of oil supply is the second. An appropriate increase is conducive to lubrication， but the improvement of lubrication effect is limited after exceeding a certain value； the nozzle height has the least influence； however， the height has the optimal value. To ensure safety， it should be put away from the gear properly. Oil-air lubrication has good cooling effect， and the transmission efficiency is better than splash lubrication under the same load condition. This research could provide technical guidance for the application of oil-air lubrication in gear transmission.